(untitled) (Medico Legal Update, 2020)
The present study was investigate to study the effects of castor leaf extract on histological healing rates of skin wounds in rabbits. sixteen adult clinically healthy rabbits from both sexes weighing from (1.25- 2 kg) were used. All animals were created wound (4cm2) full-thickness in abdominal region .The treated group (B) application of the extract on the wound to all animals while group A (control group) leave without treatment. On day 3, 7, 14 and 21 post operations collect skin tissue biopsy samples for histopathological examination each time two rabbits. The result revealed, Clinically, the rate of wound healing was same in two groups, no differences when section taken from the edge of the wounds, histopathological result was show: In 3rd day of skin wound healing group (A) (control group) show demarcation line consisted of polymorphonuclear (PMN), there was thickened at cut edges of epidermis with inflammatory cells, the inflammatory responses of group (B) (treated group) were observed in low range than the control groups. In 7th day of skin wound healing group (A) show few small vessels were present and tensile strength of the tissue by organized collagen fibers, group (B) show good tensile strength, increased in small vessels and better wound healing. In 14th day of skin wound healing group (A) show vascular density was noticeable, group (B) show increased vascular density than in group (A).